Homoeopathic Management of Breast Fibroadenoma—An Open Label, Single Arm, Observational Trial - Shukla, Purnima; Misra, Purak; Misra, Rajiv Kumar; Jain, Rishabh Kumar; Shukla, Rakesh; Manchanda, R.K; Khurana, Anil (Homœopathic Links, 2020)
Background Fibroadenoma of breast is the commonest ailment of women with significant morbidity. Available literature revealed that breast tumour recedes by homoeopathic treatment.The present study evaluated the role of homoeopathic treatment on breast fibroadenoma by using ‘Triple assessment criteria’ and to explore the mechanism, whether homoeopathic medicines bring their therapeutic effect by altering the oestrogen and progesterone receptor (ER/PR) status on tumour tissue.Materials and Methods An open label, prospective, single arm, observational study was conducted on 64 female patients having fibroadenoma of breast. Triple assessment criteria were used to explore the effectiveness of homoeopathic treatment on breast fibroadenoma. Individualised homoeopathic medicines were prescribed. The outcome measures were changes in clinical picture, number and size of lump by ultrasonomammography. ER/PR study was performed by immunohistochemistry using quick score analysis.Results Post-treatment response of 23 cases (35.93%) of fibroadenoma revealed disappearance of lump. Partial improvement was noticed in 22 cases (34.37%) with significant reduction in mean size (p < 0.001). Similarly significant reduction in number of lesions was seen in fibroadenoma (p <0.05). Conium maculatum and Phytolacca decandra were found to be the most useful remedies. Quick score value of ER after treatment showed significant reduction (Z = 4.910).Conclusion The study revealed that the therapeutic effects of individualised homoeopathic medicines play significant role in management of fibroadenoma of breast. The results of ER/PR show significant reduction in ER suggesting that homoeopathic medicines have some inhibitory effect on ER.
Keywords: fine-needle aspiration cytology (FNAC); ultrasonomammography; oestrogen receptor (ER); progesterone receptor (PR); homoeopathy; breast fibroadenoma